Marginalization of Women in Public Sphere Affirmative Policy and Economic Precarity National - M. Abrar Dahlan; Abdurrahman Irfan; Zulfia Farhana; Dewi Fauziah Nuraini; Yusna Zaidah; Muhammad Taufik Hidayat (Legtimacy: Journal of Law and Islamic Law, 2026)
This study examines the structural marginalization of women in Indonesian public spaces, focusing on political representation and industrial relations. Using normative-empirical legal research methods, this article analyzes the failure of the thirty percent affirmative quota and unilateral termination practices against pregnant workers. Findings reveal that the quota policy has failed due to administrative formalism within political parties and institutional resistance from the General Elections Commission. Meanwhile, market flexibility introduced by the Job Creation Law has exacerbated the economic precarity of female workers through contract manipulation to dismiss pregnant women. These phenomena demonstrate an ontological disconnection between constitutional rights guarantees and sociopolitical reality, rooted in an androcentric patriarchal legal culture. This study concludes that national law requires a radical reorientation toward gender-responsive substantive justice, supported by firm imperative sanctions to dismantle systemic bias within state institutions and private corporations, ensuring comprehensive human rights protection for all women in contemporary Indonesia.